The effect of regional integration on the efficiency of enterprise resource allocation - Kedong Wu; Songming Yang; Yumo Li; Mengchun Zhu (Scientific Reports)
Abstract Based on a micro-entity perspective, this paper empirically examines the effect of regional integration on the efficiency of enterprise resource allocation. Firstly, regional integration can significantly reduce the degree of resource mismatch of enterprises and improve the efficiency of resource allocation of enterprises overall. Secondly, regional integration can improve the efficiency of resource allocation of enterprises mainly through three channels, which are alleviating the financing constraints of enterprises, improving the degree of talent agglomeration, and reducing the operating costs of enterprises. Thirdly, the effect of regional integration on improving the efficiency of enterprise resource allocation is heterogeneous, which has a greater effect on the efficiency of resource allocation for state-owned enterprises, enterprises in non-monopoly industries, large-scale enterprises, and enterprises in coastal areas. Finally, regional integration improves the productivity of enterprises by optimizing their resource allocation level. The enterprise management level positively moderates the effect of regional integration on the efficiency of enterprise resource allocation. Therefore, some countermeasures and suggestions are put forward.